Office workers' perspectives on physical activity and sedentary behaviour: a qualitative study - Lorraine L. Landais; Judith G. M. Jelsma; Idske R. Dotinga; Danielle R. M. Timmermans; Evert A. L. M. Verhagen; Olga C. Damman (BMC, 2022)
Abstract Background Office workers spend a significant part of their workday sitting. Interventions that aim to reduce sedentary behaviour and increase physical activity might be more effective if greater attention is paid to individual perspectives that influence behavioural choices, including beliefs and values. This study aimed to gain insight into office workers' perspectives on physical activity and sedentary behaviour. Methods Sixteen Dutch office workers (50% female) from different professions participated in semi-structured face-to-face interviews in March 2019. To facilitate the interviews, participants received a sensitizing booklet one week before the interview. The booklet aimed to trigger them to reflect on their physical activity and sedentary behaviour and on their values in life. All interviews were audiotaped, transcribed verbatim and coded following codebook thematic analysis. Results Six themes were identified: 1) beliefs about health effects are specific regarding physical activity, but superficial regarding sedentary behaviour; 2) in addition to 'health' as a value, other values are also given priority; 3) motivations to engage in physical activity mainly stem from prioritizing the value 'health', reflected by a desire to both achieve positive short/mid-term outcomes and to prevent long-term negative outcomes; 4) attitudes towards physical inactivity and sedentary behaviour are diverse and depend on individual values and previous experiences; 5) perceived barriers depend on internal and external factors; 6) supporting factors are related to support and information in the social and physical environment. Conclusions The great value that office workers attach to health is reflected in their motivations and attitudes regarding physical activity. Increasing office workers' knowledge of the health risks of prolonged sitting may therefore increase their motivation to sit less. Although 'health' is considered important, other values, including social and work-related values, are sometimes prioritized. We conclude that interventions that aim to reduce sedentary behaviour and increase physical activity among office workers could be improved by informing about health effects of sedentary behaviour and short/mid-term benefits of physical activity, including mental health benefits. Moreover, interventions could frame physical activity as congruent with values and support value-congruent choices. Finally, the work environment could support physical activity and interruption of sedentary behaviour.